Pesquisa exploratória sobre a inclusão produtiva: análise do Prêmio SEBRAE Prefeito Empreendedor nos municípios de São Paulo - Hid, Dennys Salomão (2013)
This research investigated the fight against poverty trought public policy of productive inclusio, model of action that directs public investments for micro entrepeneurs, contributing to the heterogeneity and the reduction of the social difference. Explore the projects of implemented inclusion, in the last six years, in the cities of São Paulo enrolled in the SEBRAE Mayor entrepeneur award, wich held its 7th edition in 2012 and is organized by the brazilian servisse of support for micro and small enterprises (SEBRAE), a non-profit organization whose goal is to encourage the development of micro and small businesses. As na object of study, it was used the Paulista Guide, a publication of SEBRAE, that details the projects implemented by the mayors participants of the award. Brings together the main productive actions of initiatives inclusion, wich were evaluated by the judges and guests, providing and excellent material for a categorical analysis. The reports of these projects allowed to survey data. Trought these inventary was possible to isolate the various elemento focused and sort them by their main characteristics. The reunification of these data in tem pre-defined categories tax incentives, credit and microfinance, cooperatives, market access, formalization, incubators, debureaucrastization, clusters, education and training, and other projects allowed the visualization of the number of projects by category and development of the categories themselves over the past six years. Became evidente that the mayors enrolled seek cancel the steady state of your location trough the development and accumulation of human and economic resources, using endogenous development strategies and local. Each municipality adopts a kind of strategy, either radical or by small steps. It was possible to observe that the inclusion public policies envolve local actors public power, ptivate power and social groups and are being created from regional problems, avoiding the mimetism in implemented projects. It was realized that while municipalities have different characteristics, they have similar problems, as the high volume os workers in the informal market, the bureaucratic slowness and the absence of skilled labor. It was also clear that, the more commom is the problem, higher is the chance to adapt and replicate the project in the other locations seeks fix it or minimize it